التعليل الصوتي لمظاهر الاعلال بين النحويين المتقدمين والمتأخرين - محمد, كريم مزعل (lark, 2019)
Vowel  change (Ilal) is a common term in the morphology of  the Arabic language , and is related to phonology and dialects . It is important in Arabic language studies as a phono-logical phenomenon that is governed by precise rules the purpose of which is to create eu-phony . The paper deals with the types and the classification of the vowel changes and investigates the controversy between the traditional and the modren scholars , with an attemp to see the differeneces and similarities between their morphological view point .